1995
DOI: 10.1007/bf00023971
|View full text |Cite
|
Sign up to set email alerts
|

Production and field performance of transgenic alfalfa (Medicago sativa L.) expressing alpha-amylase and manganese-dependent lignin peroxidase

Abstract: Transgenic alfalfa plants expressing Bacillus licheniformis alpha-amylase and manganese-dependent lignin peroxidase (Mn-P) from Phanerochaete chrysosporium were produced using the Agrobacterium tumefaciens transformation system . In each case, there was a range of expression of the introduced gene among independent transgenic plants . Plants producing alpha-amylase showed no alteration of phenotype . Production of Mn-P in alfalfa, however, in most cases adversely affected plant growth and development . Affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(46 citation statements)
references
References 31 publications
0
45
1
Order By: Relevance
“…However, there is precedence for the same or similar elements of nitrogen-assimilating genes controlling expression in leaves and nodules. A 132-bp element in the pea GS3A gene has been shown to function in alfalfa leaves and nodules and was qualitatively equivalent to the 1800-bp "fulllength" promoter (Brears et al, 1991). lmprovement of nitrogen metabolism has been a longterm goal in agricultura1 research (Vance and Graham, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is precedence for the same or similar elements of nitrogen-assimilating genes controlling expression in leaves and nodules. A 132-bp element in the pea GS3A gene has been shown to function in alfalfa leaves and nodules and was qualitatively equivalent to the 1800-bp "fulllength" promoter (Brears et al, 1991). lmprovement of nitrogen metabolism has been a longterm goal in agricultura1 research (Vance and Graham, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Sequence analysis of pBICAS-GUS demonstrated that the insert was correctly cloned. Transgenic M. sativa cv Regen SY plants were obtained via Agrobacterium-mediated transformation, essentially by the method of Austin et al (1996). After rooting, plants were inoculated with R. meliloti 102F51.…”
Section: Plasmid Construction and Alfalfa Transformationmentioning
confidence: 99%
“…Poplar transformation followed the procedure in Han et al, 2000. Alfalfa transformation followed the procedure in Austin et al, 1995. …”
Section: Apoplastic Invertase Vector Construction and Plant Transformmentioning
confidence: 99%
“…Leaf discs from N. tabacum and M. sativa and cotyledons from Trifolium species were transformed using Agrobacterium-mediated transformation and plant regeneration protocols as described (Blaydes, 1966;An, 1985;Horsch et al, 1985;Bingham, 1991;Shetty and McKersie, 1993;Voisey et al, 1994;Austin et al, 1995).…”
Section: Genetic Constructs Plant Transformation and Regenerationmentioning
confidence: 99%